CCL22-Producing Resident Macrophages Enhance T Cell Response in Sjögren's Syndrome - Ushio, Aya; Arakaki, Rieko; Otsuka, Kunihiro; Yamada, Akiko; Tsunematsu, Takaaki; Kudo, Yasusei; Aota, Keiko; Azuma, Masayuki; Ishimaru, Naozumi (Frontiers in Immunology, 2018)
Macrophages (MΦs) are critical regulators of immune response and serve as a link between innate and acquired immunity. The precise mechanism of involvement of tissue-resident MΦs in the pathogenesis of autoimmune diseases is not clear. Here, using a murine model for Sjögren’s syndrome (SS), we investigated the role of tissue-resident MΦs in the onset and development of autoimmunity. Two unique populations of CD11bhigh and CD11blow resident MΦs were observed in the target tissue of the SS model. Comprehensive gene expression analysis of chemokines revealed effective production of CCL22 by the CD11bhigh MΦs. CCL22 upregulated the migratory activity of CD4+ T cells by increasing CCR4, a receptor of CCL22, on T cells in the SS model. In addition, CCL22 enhanced IFN-γ production of T cells of the SS model, thereby suggesting that CCL22 may impair the local immune tolerance in the target organ of the SS model. Moreover, administration of anti-CCL22 antibody suppressed autoimmune lesions in the SS model. Finally, histopathological analysis revealed numerous CCL22-producing MΦs in the minor salivary gland tissue specimens of the SS patients. CCL22-producing tissue-resident MΦs may control autoimmune lesions by enhancing T cell response in the SS model. These results suggest that specific chemokines and their receptors may serve as novel therapeutic or diagnostic targets for SS.